Ga–Sb–S Chalcogenide Glasses for Mid‐Infrared Applications. Issue 1 (18th November 2015) - Yang, Anping; Zhang, Mingjie; Li, Lei; Wang, Yuwei; Zhang, Bin; Yang, Zhiyong; Tang, Dingyuan
Abstract : In this study, a novel chalcogenide glass system, Ga–Sb–S, is reported. The glass‐forming ability, the physical properties, and the structure are investigated; and the potential applications of the glasses are evaluated. The compositions consisting of ~3%–10% Ga, ~29%–37% Sb, and ~57%–63% S can form glasses. The glasses have a wide transparent window of ~0.8–14 μm, high linear refractive indices of ~2.62–2.70 (@10 μm), high third‐order nonlinear refractive indices of ~12.4 × 10 −14 cm 2 /W (@ 1.55 μm), low phonon energy, and large rare earth solubility. These favorable properties make them promising materials for mid‐infrared applications such as thermal imaging, nonlinear optics, and lasers.